Sentence Processing in Spanish as a Heritage Language: A Self‐Paced Reading Study of Relative Clause Attachment. Issue 3 (14th April 2018) - Jegerski, Jill
Abstract: Heritage Spanish is often influenced by English, and previous research on late Spanish‐English bilinguals suggests that their relative clause attachment preferences in Spanish are affected by English exposure. Nevertheless, recent work with heritage speakers has revealed that early (high‐proficiency) Spanish‐English bilinguals demonstrate a monolingual‐like high‐attachment preference in Spanish. Offline data from this self‐paced reading study showed the same preference for bilinguals of intermediate proficiency in a meaning‐oriented rather than a metalinguistic task. However, unlike in previous research, a group of late bilinguals also showed high‐attachment preference, possibly because of insufficient exposure to English. Online data showed no effects for either bilingual group and a nonsignificant numerical trend toward high attachment for a monolingual group. Thus, even moderately proficient heritage speakers seem to be adept at managing interaction between two language systems, so it appears not to affect their interpretation of relative clauses.